Laminate film, constituent body, head-up display system, and transportation vehicle

JP2025032476APending Publication Date: 2025-03-12TORAY INDUSTRIES INC
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2023137754
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-08-28
Publication Date
2025-03-12

AI Technical Summary

Benefits of technology

【0009】 本発明により、当該課題を解決し、輸送用機器の風防の最表面に貼合したときの外観不良の軽減と、耐摩耗性を両立した積層フィルムを提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025032476000001
    Figure 2025032476000001
  • Figure 2025032476000002
    Figure 2025032476000002
  • Figure 2025032476000003
    Figure 2025032476000003
Patent Text Reader

Abstract

To provide a laminate film that satisfies both reduction of appearance defects and abrasion resistance when laminated on the outermost surface of a windshield of a transportation vehicle.SOLUTION: A laminate film comprises a protective layer at least on one surface of a substrate layer, and has at least one reflection band (reflection band A) in which the reflectance of P wave that is made incident to the protective layer in the condition of a wavelength 400 to 2000 nm and an incident angle 60° becomes 10% or more continuously for 100 nm or more, where the density of inorganic particles of the protective layer is 10 mass% or more and 60 mass% or less, and the inorganic particle occupancy of the outermost surface of the protective layer is 0.1% or more and 60% or less.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a laminate film, a structure, a head-up display system, and transportation equipment having excellent image display properties. [Background technology]

[0002] A head-up display system is a display system that projects information into the field of vision of a passenger in a vehicle or other transportation device, and improves driving safety and comfort by displaying, for example, route information, caution information, building information, etc., that matches the scenery in front of the passenger. The simplest mechanism is to project an image from an image projector at an oblique angle onto a projection section on the windshield (e.g., the windshield) of the transportation device, reflect the image, and bring the reflected image into the field of vision of the passenger.

[0003] As an example of the configuration of the projection section on the windshield of a head-up display, a configuration in which a film with polarizing reflection properties is inserted between two pieces of glass is shown (Patent Document 1). However, in this configuration, unless an image is projected at a specific angle of incidence called Brewster's angle, a reflected image occurs on the glass surface on the image projector side in addition to the reflected image on the film. Therefore, in this configuration, a so-called double image is visible, impairing display performance.

[0004] In order to suppress double images, a configuration has been proposed in which a base layer having reflective properties is attached to the top surface of the glass surface on the image projector side via an adhesive layer (Patent Documents 2 and 3). With such a configuration, the image is reflected by the base layer surface having reflective properties before the glass, so that double images caused by reflection on the glass surface can be suppressed. On the other hand, since the base layer is exposed in such an embodiment, it is necessary to provide a protective layer such as a hard coat on the top surface of the base layer to protect the base layer from scratches. However, the windshield of a transportation device is not flat but has a three-dimensional curved structure, and when a base layer having a protective layer is attached to the windshield, there is a risk of appearance defects such as wrinkles and cracks in the protective layer. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Special Publication No. 2006-512622 [Patent Document 2] JP 2009-42647 A [Patent Document 3] Patent Publication No. 2022-81716 Summary of the Invention [Problem to be solved by the invention]

[0006] As a method for suppressing such poor appearance, there is a method of shrinking the base layer by a certain amount at a high temperature of 100°C or more during the lamination process while following the curved surface. However, when a general protective layer such as that disclosed in Patent Documents 2 and 3 is applied to this application, if the abrasion resistance is improved, the shrinkage may be insufficient and the protective layer may crack during lamination. Conversely, if the shrinkage is increased to enable high-quality lamination, the abrasion resistance may be insufficient and scratches may easily occur when dirt is wiped with a cloth or the like. In other words, a film having a general protective layer has a trade-off relationship between shrinkage (processability) and abrasion resistance or hardness, making it difficult to apply to this application. Therefore, the present invention aims to solve the problem and provide a laminated film that achieves both reduced poor appearance and abrasion resistance when laminated to the outermost surface of the windshield of a transportation device. [Means for solving the problem]

[0007] The present invention has been made to solve the above problems and has the following configuration: Namely, the laminate film is characterized in that it has a protective layer on at least one surface of a base layer, has at least one reflection band (reflection band A) in which the reflectance of P waves incident on the protective layer under conditions of a wavelength of 400 to 2000 nm and an incident angle of 60° is 10% or more continuously over 100 nm or more, has an inorganic particle concentration of 10% or more by mass and 60% or less by mass, and has an inorganic particle occupancy rate of the outermost surface of the protective layer of 0.1% or more and 60% or less.

[0008] The laminated film of the present invention can also be in the following embodiments, and can also be used in structures, head-up display systems, and transportation equipment as described below. (1) A laminate film comprising a protective layer on at least one surface of a base layer, and at least one reflection band (reflection band A) in which the reflectance of P waves incident on the protective layer under conditions of a wavelength of 400 to 2000 nm and an incident angle of 60° is 10% or more continuously over 100 nm or more, the concentration of inorganic particles in the protective layer is 10% by mass or more and 60% by mass or less, and the inorganic particle occupancy rate of the outermost surface of the protective layer is 0.1% by mass or more and 60% by mass or less. (2) The laminate film according to (1), wherein the average particle size of the inorganic particles is 5 nm or more and 60 nm or less. (3) The laminate film according to (1) or (2), wherein the protective layer has an arithmetic mean roughness of 0.10 nm or more and 0.90 nm or less. (4) The laminate film according to any one of (1) to (3), wherein the protective layer has a crack initiation pressure of 100 GPa or more and 600 GPa or less, as determined by a microscratch test method in accordance with JIS R-3255:1997. (5) The laminate film according to any one of (1) to (4), which has a heat shrinkage rate of 1.0% or more and 3.0% or less when heat-treated at 150° C. for 30 minutes. (6) The laminate film according to any one of (1) to (5), wherein the average reflectance of P waves having a wavelength of 400 to 700 nm incident on the protective layer at an incident angle of 60° is 10% or more. (7) The laminate film according to any one of (1) to (6), having at least one reflection band (reflection band B) in which the reflectance of light incident on the protective layer at a wavelength of 800 to 2000 nm and an incident angle of 0° is 30% or more continuously over a range of 100 nm or more. (8) The laminate film according to any one of (1) to (7), further comprising the protective layer on one surface of the base layer, and an adhesive layer on the surface opposite to the protective layer. (9) The laminate film according to (8), wherein the adhesive layer has an outermost layer crack initiation load of 1.0 GPa or more in a scratch test. (10) The laminated film according to (8) or (9), wherein the adhesive layer has a thickness of 5 μm or more and 25 μm or less. (11) A structure comprising a support mainly made of glass or resin and a laminate film according to any one of (8) to (10) on at least one surface of the support. (12) A head-up display system comprising an image projector that projects an image and the structure described in (11). (13) A head-up display system as described in (12), wherein the intensity of the P-wave component in the light beam projected from the image projector is 51% or more of the intensity of all light beam components. (14) A transportation device comprising the structure described in (11). Effect of the Invention

[0009] The present invention solves the above problems and provides a laminate film that reduces appearance defects when applied to the outermost surface of the windshield of a transportation device and also provides good abrasion resistance. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] The laminated film of the present invention is characterized in that it has a protective layer on at least one surface of a base layer, has at least one reflection band (reflection band A) in which the reflectance of P waves incident on the protective layer under conditions of a wavelength of 400 to 2000 nm and an incident angle of 60° is 10% or more continuously over 100 nm or more, has an inorganic particle concentration of 10% by mass or more and 60% by mass or less, and has an inorganic particle occupancy rate of the outermost surface of the protective layer of 0.1% by mass or more and 60% or less. The following describes an embodiment of the present invention, but the present invention is not limited to the embodiment including the following examples, and various modifications are naturally possible within the scope of the invention as long as the object of the invention can be achieved and the gist of the invention is not deviated from.

[0011] When the laminated film of the present invention is used as a projection member of an image display device such as a head-up display system, it is necessary to provide a protective layer on at least one surface of the base layer from the viewpoint of achieving both reduction in double images and improvement in abrasion resistance. In head-up display system applications, if a resin film having reflective properties is attached to the outermost surface on the viewing side of the windshield to suppress double images, a problem arises in that the resin film is prone to being scratched when wiped with a cloth.

[0012] When the resin film is made into a laminated film having a protective layer on at least one surface of the base layer, by laminating the film on the viewing side of the windshield so that the protective layer is located on the outermost surface, the occurrence of double images can be reduced while the abrasion resistance can be improved by the protective layer. Here, the protective layer refers to a layer in which more than 50% by mass and 100% by mass or less of the resin components constituting the layer are thermosetting resin or ultraviolet curing resin, and which is located on the outermost surface. In addition, when there are multiple layers in which more than 50% by mass and 100% by mass or less of the resin components constituting the layer are thermosetting resin or ultraviolet curing resin, starting from the outermost surface, the entire layer is treated as one protective layer (i.e., the protective layer may have either a single layer structure or a laminate structure). In addition, when multiple types of thermosetting resin or ultraviolet curing resin are included, the amount of the thermosetting resin or ultraviolet curing resin is calculated by adding up all the types. In addition, the protective layer (the layer located on the outermost surface when the protective layer is composed of multiple layers) preferably has a crack initiation load of 100 GPa or more obtained by the micro scratch test method described below. In addition, the base layer refers to a layer containing 60% by mass or more and 100% by mass or less of thermoplastic resin out of 100% by mass of the resin components constituting the layer. In addition, when such layers are continuous, they can be defined as one base layer.

[0013] It is important that the laminate film of the present invention has at least one reflection band (reflection band A) in which the reflectance of P waves incident on the protective layer at a wavelength of 400 to 2000 nm and an incident angle of 60° is 10% or more continuously over a range of 100 nm or more.

[0014] When at least a part of the reflection band A is included in the visible light region of 400 to 700 nm, a clear reflected image can be obtained when a light image of the wavelength of the reflection band A is projected onto the windshield of a transport device to which the laminated film is attached. From the viewpoint of clearly projecting an image containing more colors, it is preferable that the reflection band A covers a wider range of 400 to 700 nm. The reflection band A can be specified from the reflectance data at each wavelength measured at 1 nm intervals with the incident surface on the protective layer side and the incident angle of 60°, and the reflectance at each wavelength can be measured by a known spectrophotometer (the measurement method will be described later in detail).

[0015] Moreover, the higher the reflectance of P waves in the 400-700 nm band, the better the image display. Therefore, when at least a part of the reflection band A is included in the visible light region of 400-700 nm, it is preferable that there is a region in the reflection band A where the reflectance of P waves is 20% or more continuously over 100 nm or more. On the other hand, if the reflectance of P waves is too high in the 400-700 nm band, there is a problem that the visibility of the outside world through the windshield is poor. From this point of view and from the viewpoint of feasibility, it is preferable that there is no region in the reflection band A where the reflectance of P waves is 70% or more continuously over 100 nm or more.

[0016] In addition, when the reflection band A does not overlap with the visible light region and exists in the band of 750 nm to 2000 nm, the laminated film of the present invention does not reflect the visible light region but reflects infrared rays. Therefore, it is transparent but has excellent heat shielding properties, and can be attached to window glass or the like to be used as a heat shielding film. In addition, since the higher the reflectance in the band, the better the heat shielding properties of the laminated film of the present invention, it is preferable that the reflection band A has a region in which the reflectance of P waves is 70% or more continuously over 100 nm or more.

[0017] As a method for making the laminated film have at least one reflection band A, a method of using a reflective film having such reflection characteristics as a base layer of the laminated film can be mentioned.

[0018] An example of such a reflective film will be described below. Such a reflective film can be obtained by, for example, stacking a plurality of different thermoplastic resin layers in a regular pattern of 51 layers or more, preferably 401 layers or more, and more preferably 601 layers or more. Here, the thermoplastic resin layers are different in composition and have refractive indices that differ by 0.01 or more in either the orientation axis direction, the direction perpendicular to the orientation axis in the film plane, or the direction perpendicular to the film plane. There is no particular upper limit on the number of layers, but considering the deterioration of handling due to the increase in thickness and the need for a larger device, the upper limit is about 2001 layers.

[0019] The difference in composition means that the components constituting the thermoplastic resin layer are different by 1 mol % or more. The orientation axis direction means the direction in the film plane where the refractive index is the highest. This can be specified by a known measurement method, and for example, a molecular orientation meter MOA-8000 manufactured by Oji Instruments Co., Ltd. can be used for the measurement. In addition, the refractive index of the orientation axis direction in the film plane of the thermoplastic resin layer constituting the outermost layer among the layers, the direction perpendicular thereto, and the direction perpendicular to the film plane can be measured by a known measurement method. The critical angle method can be used as the measurement method, and an Abbe refractometer can be used as the device.

[0020] The refractive index in the direction of the main orientation axis in the plane of the thermoplastic resin film constituting the layers other than the outermost layer, the direction perpendicular thereto, and the direction perpendicular to the film surface are determined as follows. Using the thickness of each layer of the reflective film and the refractive index of the thermoplastic resin layer constituting the outermost surface, the refractive index of each layer other than the outermost layer is set to an arbitrary value, and an optical simulation of the reflectance is performed. Next, from the optical simulation result and the reflectance measured by the measurement method described below, the average reflectance of the reflection band that is 10% or more continuously over 100 nm or more of the wavelength of 400 to 2000 nm is calculated, and if the difference between the two is ±2% or less, the refractive index is determined as the refractive index of each layer other than the outermost layer. The thickness of each layer of the reflective film can be measured by observing a sample cut into a cross section using a microtome, using a transmission electron microscope (TEM), for example, H-7100FA type (manufactured by Hitachi, Ltd.). In addition, the optical simulation can be calculated using a VBA program using the characteristic matrix method of optical thin films (Mitsunobu Kohiyama (2006). Optical Thin Film Filter Design, Optronics Co., Ltd.).

[0021] Regularly laminated means that a plurality of different thermoplastic resin layers are laminated in a regular arrangement in the thickness direction. For the purpose of simplifying the explanation, a part of the explanation will be explained by taking as an example a reflective film having a configuration in which two different thermoplastic resin layers are alternately laminated, which is one of the preferred embodiments of the present invention, but the same should be understood when three or more types of thermoplastic resins are used.

[0022] Specific examples of such an embodiment include those in which the reflective film is made of a layer (layer A) made of a first thermoplastic resin and a layer (layer B) made of a second thermoplastic resin, and the layers are laminated in this order, such as A(BA)n and B(AB)n (n is a natural number representing the number of repeating units, the same applies below). In addition, in the case where the reflective film is made of a layer (layer A) made of a first thermoplastic resin, a layer (layer B) made of a second thermoplastic resin, and a layer (layer C) made of a third thermoplastic resin, the arrangement is not particularly limited, and examples include those in which the layers are laminated in this order with a certain regularity, such as C(BA)nC, C(ABC)n, and C(ACBC)n. By alternately laminating a plurality of thermoplastic resin layers having different optical properties such as refractive index in this way, it becomes possible to develop interference reflection that selectively reflects light in a desired wavelength band due to the difference in refractive index in the in-plane direction of each layer, the difference in refractive index in the thickness direction, and the relationship with the layer thickness. In particular, by controlling the thickness of each layer, it is possible to selectively reflect light in the visible light region of 400 to 700 nm and the infrared region of 800 to 2000 nm.

[0023] As a method for providing the reflective film with the reflective band A, for example, a method of adjusting the refractive index difference in the thickness direction between two thermoplastic resin layers in the reflective film can be used. More specifically, the refractive index difference is preferably 0.030 or more, more preferably 0.050 or more. In addition, by making the refractive index difference 0.060 or more, a region in which the reflectance of P waves is 20% or more continuously over 100 nm or more can be formed in the reflective band A. In addition, when the reflective band A is in the visible light region, the refractive index difference in the direction parallel to the film surface between the two thermoplastic resin layers (in-plane average refractive index difference) is preferably small because the light transmittance from the front increases and the transparency is improved, and the refractive index difference is more preferably 0.025 or less, and even more preferably 0.020 or less. The thickness direction refers to the direction perpendicular to the film surface, and the in-plane average refractive index refers to the average value of the refractive index in the orientation axis direction and the refractive index in the direction perpendicular to the orientation axis direction in the film plane.

[0024] In addition to the reflective film in which a plurality of different thermoplastic resins are regularly laminated, the reflective band A can also be formed by a reflective film in which one or more metal thin layers are laminated on a transparent substrate (hereinafter referred to as a metal sputtered film). To obtain such a reflective film, a metal sputtering method can be used. The metal sputtering method is a method in which an inert gas such as Ar is introduced into the air, a negative voltage is applied to the transparent substrate to generate a glow discharge to ionize the inert gas atoms, and the gas ions are collided with the surface of the target at high speed, striking it violently while violently ejecting metal atoms and metal oxide molecules, which are then vigorously attached and deposited on the surface to form a thin film. The reflective band and reflectance can be controlled by adjusting the type and thickness of the metal atoms and metal oxide molecules to be laminated, and the reflective band A can be formed by using a preferred type and thickness of the metal / metal oxide.

[0025] In the laminated film of the present invention, from the viewpoint of achieving both the processability and abrasion resistance of the protective layer, the concentration of inorganic particles in the protective layer is preferably 10% by mass or more and 60% by mass or less. The concentration of inorganic particles in the protective layer can be calculated as a value when all components constituting the protective layer are 100% by mass. The protective layer can be formed, for example, by radically polymerizing an organic monomer such as acrylic by UV irradiation, and growing and curing a polymer chain having a crosslinking point. The processability (shrinkage and flexibility) and abrasion resistance and hardness of the protective layer can be controlled by adjusting the monomer type and the amount of crosslinking points, but generally, these are in a trade-off relationship and it is difficult to achieve both.

[0026] However, by adding inorganic particles to the protective layer, it is possible to improve the abrasion resistance and hardness. Therefore, by adding inorganic particles to an organic protective layer that is excellent in processability but poor in hardness and abrasion resistance, it is possible to achieve both high processability and hardness and abrasion resistance. From this viewpoint, in the laminated film of the present invention, the concentration of inorganic particles in the protective layer needs to be 10% by mass or more and 60% by mass or less. If the concentration of inorganic particles in the protective layer is less than 10% by mass, the effect of improving hardness and abrasion resistance is not sufficient. In addition, usually, the higher the concentration of inorganic particles in the protective layer, the greater the effect of improving hardness and abrasion resistance can be expected, but if the concentration of inorganic particles in the protective layer exceeds 60% by mass, the hardness of the protective layer becomes too high, reducing the processability, and the occurrence of scratches due to particle drop-off during wear increases, thereby worsening the abrasion resistance. From the above viewpoint, it is preferably 20% by mass or more and 50% by mass or less.

[0027] In the laminated film of the present invention, the inorganic particle occupancy rate of the outermost surface of the protective layer must be 0.1% or more and 60% or less. By adopting such an embodiment, it is possible to impart high abrasion resistance to the protective layer. Here, the inorganic particle occupancy rate refers to the area ratio of the inorganic particle portion that occupies the outermost surface of the protective layer, and can be calculated using analysis software from an image obtained by observing the surface with a SEM (the measurement method will be described in detail later). The inorganic particle occupancy rate of the outermost surface of the protective layer increases as the number of inorganic particles present on the outermost surface of the protective layer increases.

[0028] When the inorganic particle occupancy rate of the outermost surface of the protective layer exceeds 60%, the abrasion resistance of the protective layer is significantly deteriorated and scratches are easily generated. In a general abrasion resistance test, a test piece (cloth such as wool) with a rough surface on the microscale is pressed against the protective layer and the occurrence of scratches is evaluated when the test piece is reciprocated hundreds to tens of thousands of times. Scratches on the protective layer containing inorganic particles are mainly generated when the surface of the test piece is caught by the particles present on the outermost surface of the protective layer, causing the particles to fall off and stress to concentrate at that point. Therefore, the lower the inorganic particle occupancy rate of the outermost surface of the protective layer, the less the test piece and the particles are caught, and the more the abrasion resistance of the protective layer is improved. From the above viewpoint, the inorganic particle occupancy rate of the outermost surface of the protective layer is preferably 50% or less. In addition, the lower limit of the inorganic particle occupancy rate of the outermost surface of the protective layer is 0.1% from the viewpoint of feasibility based on the fact that the concentration of inorganic particles in the protective layer is at least 10% by mass, but in reality it is 10%.

[0029] The inorganic particle occupancy rate of the outermost surface of the protective layer is usually proportional to the inorganic particle concentration contained in the protective layer, so it can be controlled by adjusting the inorganic particle concentration in the protective layer. On the other hand, as a method for lowering the inorganic particle occupancy rate of the outermost surface while maintaining the inorganic particle concentration in the protective layer, a method of forming a layer having a laminated structure by forming a layer that is particle-free or has a smaller amount of inorganic particles and is a thermosetting resin or an ultraviolet curing resin in 100 mass% of the resin components constituting the layer as a top coat layer on the layer containing inorganic particles can be mentioned. By adopting such an embodiment, the hardness and processability of the entire protective layer are improved because the inorganic particles are contained in large amounts, while the inorganic particle occupancy rate of the outermost surface is reduced, so that the occurrence of scratches due to particle drop-off during wear is suppressed. A hard coat (hereinafter sometimes referred to as HC) used in the top coat layer is preferably one with high hardness, but such a coat has low processability accordingly, and the thicker it is, the lower the processability of the entire protective layer becomes. Therefore, the maximum thickness of the protective layer including the top coat layer is preferably 15 μm. In such an embodiment, the thermosetting resin or the UV-curable resin in the layer containing inorganic particles and the top coat may be the same or different.

[0030] In the laminated film of the present invention, from the viewpoint of achieving both transparency and reducing the occurrence of scratches due to abrasion, the average particle size of the inorganic particles is preferably 5 nm or more and 60 nm or less. By setting the average particle size of the inorganic particles to 60 nm or less, even if the rough test piece surface used in the abrasion resistance test is pressed against the microscale, the particles present on the outermost surface of the protective layer are unlikely to be caught, and the detachment of the particles and the occurrence of scratches associated therewith can be reduced. In addition, when the average particle size of the inorganic particles is 60 nm or less, even if the inorganic particles aggregate, the scattered light has a wavelength outside the visible light region according to the Stokes-Einstein equation, so that the cloudiness of the protective layer is reduced and the transparency is increased. From the above viewpoint, the average particle size of the inorganic particles is more preferably 30 nm or less. From the above viewpoint, the smaller the average particle size of the inorganic particles, the more preferable, but from the viewpoint of feasibility, the lower limit is 5 nm, and in reality, 10 nm is more preferable. The transparency of the laminated film can be evaluated by measuring the internal haze, as described later.

[0031] The average particle size of the inorganic particles can be measured by observing a cross section of the laminated film cut in a direction perpendicular to the film surface with a scanning electron microscope (the detailed measurement method will be described later).

[0032] The method for forming the protective layer of the laminated film of the present invention is not particularly limited, but coating with a coating composition can be preferably used. The coating composition preferably contains a solvent, a binder component, a photopolymerization initiator, inorganic particles, other additives, etc., and can achieve its function by controlling the type, physical properties, and amount of each material. As described above, when the protective layer has a two-layer structure, for example, and the particle amount is made different between the layer formed first and the top coat layer, which is the outermost layer, it is preferable to make the inorganic particle amount different between the coating composition for forming the layer formed first and the coating composition for forming the top coat layer.

[0033] The type of solvent in the coating composition for forming the protective layer of the laminated film of the present invention is not particularly limited, but usually, a solvent having a boiling point of 250° C. or less at normal pressure is preferred. Specifically, water, alcohols, ketones, ethers, esters, hydrocarbons, amides, fluorine-containing compounds, etc. can be used. These can be used alone or in combination of two or more.

[0034] The binder component refers to a material that is soluble in a solvent and can harden a coating film by volatilization of the solvent and its own polymerization and crosslinking reaction, and the state after hardening is called a binder. The binder component in the coating composition for forming the protective layer of the laminated film of the present invention is not particularly limited, and may be one type or may be used in combination with two or more types. In addition, the binder component is preferably a material that can be polymerized by using a photopolymerization initiator that can be cleaved by active energy rays and can harden a coating film.

[0035] Specifically, when ultraviolet (UV) rays are used as the active energy rays and a photopolymerization initiator is used in combination, preferred monomer types that serve as binder raw materials include polyfunctional (meth)acrylate monomers, (meth)acrylate oligomers, alkoxysilanes having a (meth)acrylic group, alkoxysilane hydrolysates having a (meth)acrylic group, alkoxysilane oligomers having a (meth)acrylic group, acrylic polymers having a (meth)acrylic group, urethane polymers having a (meth)acrylic group, epoxy polymers having a (meth)acrylic group, silicone polymers having a (meth)acrylic group, and the like.

[0036] Examples of polyfunctional (meth)acrylate monomers include polyfunctional acrylates having two or more (meth)acryloyloxy groups in one molecule and modified polymers thereof, and specific examples thereof include pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol tri(meth)acrylate, dipentaerythritol tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, dipentaerythritol hexa(meth)acrylate, trimethylolpropane tri(meth)acrylate, pentaerythritol triacrylate, hexanemethylene diisocyanate, and urethane acrylate. These monomers can be used alone or in combination of two or more.

[0037] The acrylic polymer having a (meth)acrylic group is preferably synthesized by a polymerization reaction of a multifunctional acrylate monomer (e.g., polyol acrylate, polyester acrylate, urethane acrylate, epoxy acrylate). In addition, a silicone polymer which is a co-hydrolyzate of a silane compound having a methacrylic group (e.g., tetraalkoxysilane, alkyltrialkoxysilane) and a silane coupling agent is also preferably used.

[0038] As the photopolymerization initiator, various types can be used, for example, a photoradical polymerization initiator, a photoacid generator, or a photobase generator. However, it is preferable to use one that can initiate or promote polymerization and / or silanol condensation and / or crosslinking reaction of the binder in the coating composition by radical polymerization reaction or the like.

[0039] The coating composition used to form the protective layer of the laminated film of the present invention contains an inorganic particle dispersion. The inorganic particles contained in the inorganic particle dispersion are not particularly limited, but are preferably at least one selected from the group consisting of metal elements, semimetal elements, and their oxides, nitrides, borides, carbonates, and sulfates, and are more preferably oxide particles of at least one element selected from Si, Na, K, Ca, Mg, Ga, Zr, Ti, Al, In, Sb, Sn, and Ce. Specifically, silica (SiO2), zirconium oxide (ZrO2), titanium oxide (TiO2), aluminum oxide (Al2O3), indium oxide (In2O3), zinc oxide (ZnO), tin oxide (SnO2), antimony oxide (Sb2O3), and indium tin oxide can be preferably used. These inorganic particles may be used alone or in combination.

[0040] In the laminated film of the present invention, the arithmetic mean roughness of the protective layer is preferably 0.10 nm or more and 0.90 nm or less. By adopting such an embodiment, even if a wear resistance test is performed by pressing a rough test piece surface against the protective layer, the surface is smooth and therefore less likely to be scratched. The lower the arithmetic mean roughness, the smoother the surface, which is preferable, but from the viewpoint of feasibility, the lower limit is 0.10 nm. From the above viewpoint, the arithmetic mean roughness is more preferably 0.30 nm or more and 0.70 nm or less.

[0041] Since the inorganic particle occupancy rate on the outermost surface of the protective layer and the average particle diameter in the protective layer affect the arithmetic mean roughness of the protective layer, for example, a method of adjusting these to be small can be used to reduce the arithmetic mean roughness of the protective layer. The arithmetic mean roughness of the protective layer can be measured using a known scanning white light interference microscope, and for example, Hitachi High-Tech Science Corporation's "VertScan" (registered trademark) VS1540 can be used as the measuring device (the measurement method when using this device will be described in detail later).

[0042] From the viewpoint of achieving both improved processability and reduced scratches due to wear, the laminated film of the present invention preferably has a crack initiation pressure of 100 GPa or more and 600 GPa or less, which is obtained by a microscratch test method conforming to JISR-3255:1997. Here, the microscratch test method is a method of quantifying hardness in which a stylus having a diameter of several to several tens of micrometers is brought into contact with the outermost surface of a measurement target, the load applied to the stylus is measured while increasing the load over time, and the point at which the load behavior changes suddenly when the surface is scratched is taken as the crack initiation pressure (the detailed measurement method will be described later). The device for measuring the crack initiation pressure is not particularly limited as long as it is capable of measurement, and for example, a scratch tester (CSR5000 manufactured by Rhesca Co., Ltd.) can be used. Hereinafter, the "crack initiation pressure of the protective layer obtained by a microscratch test method conforming to JISR-3255:1997" may be referred to as the crack initiation pressure of the protective layer.

[0043] When the cracking pressure of the protective layer is 100 GPa or more and 600 GPa, the occurrence of scratches due to wear can be suppressed and the processability can be improved. As described above, the smoothness of the outermost surface of the protective layer is important for improving the wear resistance, but it is also important that the protective layer has a certain level of hardness or more. When the cracking pressure of the protective layer is 100 GPa or more, the protective layer has a certain level of hardness or more, so that the occurrence of scratches due to wear can be reduced. From the above viewpoint, the cracking load of the protective layer is preferably 150 GPa or more. Thus, from the viewpoint of reducing scratches due to wear, the higher the cracking load of the protective layer, the more preferable it is, but as described above, it is necessary to consider the processability during heating, which is in a trade-off relationship. From the viewpoint of maintaining good processability during heating, the upper limit of the cracking load of the protective layer is preferably 600 GPa, more preferably 500 GPa. The cracking load of the protective layer can be controlled by adjusting the concentration of inorganic particles that affect the hardness of the protective layer, or by selecting the monomer species (binder component species) for forming the protective layer.

[0044] Another method for measuring the hardness of the protective layer is pencil hardness measurement. However, when the measurement target is a laminate of multiple layers, the adhesive layer or base material, which has a lower hardness than the protective layer, is likely to be dented when the pencil lead is pressed against the measurement target, resulting in scratches with a lower hardness than the hardness of the protective layer itself. Therefore, there is also a problem that the measured value tends to be low. On the other hand, the micro scratch test method can measure the hardness at the outermost surface of the protective layer, making it possible to measure the hardness of the protective layer itself more accurately.

[0045] From the viewpoint of improving the processability during lamination, the laminated film of the present invention preferably has a heat shrinkage rate of 1.0% or more and 3.0% or less when heat-treated at 150 ° C for 30 minutes. Usually, the windshield or window of a transport device such as a vehicle has a three-dimensional curved surface, and in order to laminate the laminated film to the windshield or window without causing wrinkles, etc., it is necessary for the laminated film to have a certain degree of conformability to the three-dimensional curved surface at the temperature during processing. If the heat shrinkage rate is 1.0% or more, for example, when performing the lamination process at a high temperature of 100 ° C or more, the laminated film will heat shrink and conform to the curved surface, so that the appearance of the windshield or window after lamination can be improved, and cracks generated in the protective layer can also be reduced. From the above viewpoint, the shrinkage rate is more preferably 1.2% or more. On the other hand, the upper limit of the shrinkage rate is 3.0%, more preferably 2.0%, because it is necessary to maintain the hardness, which is in a trade-off relationship.

[0046] The shrinkage rate can be adjusted to 1.0% or more and 3.0% or less, or more preferably 1.2% or more and 2.0% or less, by, for example, adjusting the inorganic particle concentration, which is in a trade-off relationship with hardness, or by selecting the hard coat type and, in turn, the monomer type (binder component). Incidentally, it is preferable to include a urethane component in the monomer type, since it can enhance the shrinkage. In addition, the heat shrinkage rate of the base layer must also be taken into consideration in adjusting the shrinkage rate, and it is preferable to set the heat shrinkage rate of the film alone constituting the base layer to 1.0% or more and 5.0% or less, preferably 1.0% or more and 3.0% or less, when the film alone constituting the base layer is heat-treated at 150°C for 30 minutes. As a method for setting the heat shrinkage rate of the film to 1.0% or more and 5.0% or less, heating at a predetermined temperature in a heat treatment step after a stretching step in the film manufacturing method described later can be mentioned, and the heating temperature is specifically preferably 170°C to 230°C.

[0047] Here, "heat shrinkage rate when heat-treated at 150°C for 30 minutes" means the value in the direction with the largest shrinkage rate when heated under the conditions, and can be measured by the following measurement method. First, a 150mm x 10mm sample is cut out from the laminated film at random, and this is designated as sample 1. Next, a 150mm x 10mm sample is cut out so that the angle between the longitudinal direction of sample position 1 and the longitudinal direction is 10° counterclockwise, and this is designated as sample 2. Similarly, sample acquisition is repeated 10 times in total to obtain samples 3 to 10. These samples are left in an atmosphere of 23°C and 60% relative humidity for 30 minutes, and two marks are made at intervals of about 100mm in the longitudinal direction of the sample under that atmosphere. Next, the sample is left in an atmosphere of 150°C in a tension-free state for 30 minutes, and then cooled and conditioned for 1 hour in an atmosphere of 23°C and 60% relative humidity, and the interval between the marks made earlier is measured. The thermal shrinkage rate of each sample is calculated from the measurement results obtained, and the largest value is adopted as the "thermal shrinkage rate when heat treated at 150°C for 30 minutes" of the laminated film (details of the measurement method will be described later).

[0048] The laminated film of the present invention preferably has an average reflectance of 10% or more for P waves having a wavelength of 400 to 700 nm that are incident on the protective layer at an incident angle of 60°. When the reflectance of P waves in this band is 10% or more, a clear reflected image with high visibility can be obtained when an image is projected onto the windshield of a transport device to which the laminated film of the present invention is attached. Since the higher the average reflectance of P waves in this band, the higher the visibility, the more preferable the average reflectance of P waves in this band is 20% or more. On the other hand, if the average reflectance of P waves in this band is too high, the visibility of the outside world through the windshield is poor, so the upper limit of the average reflectance is preferably 70%, more preferably 45%, and even more preferably 29%.

[0049] The optical characteristics can be achieved by the same method as that for forming the reflection band A. The average reflectance of the P wave in the band can be determined from the reflectance data of the P wave at each wavelength measured at 1 nm intervals with the incident surface on the protective layer side and the incident angle of 60°, and the reflectance at each wavelength can be measured by a known spectrophotometer (the measurement method will be described in detail later).

[0050] The laminated film of the present invention preferably has at least one reflection band (reflection band B) in which the reflectance of light incident on the protective layer under conditions of a wavelength of 800 to 2000 nm and an incident angle of 0° is 30% or more continuously over 100 nm or more. Sunlight has an intensity distribution mainly in the visible light region, and the intensity distribution tends to become smaller as the wavelength increases. Although the laminated film can improve the heat shielding performance by cutting light in the visible light region, a laminated film that cuts light in the visible light region also has a reduced transparency, and may not be suitable for use in applications where transparency is required.

[0051] Therefore, in the 800 to 2000 nm band, which is a wavelength longer than the visible light region, a band is formed in which the reflectance is 30% or more continuously over 100 nm or more when light is incident on the protective layer at an incident angle of 0°, thereby imparting heat shielding properties to the laminated film. Since the higher the reflectance in the reflection band B, the more improved the heat shielding properties are, it is more preferable that the reflection band B includes a band in which the reflectance of light incident on the protective layer at an incident angle of 0° is 70% or more continuously over 100 nm or more.

[0052] As a method for obtaining a laminated film having a reflection band B, it is preferable that the difference in the in-plane average refractive index between the two thermoplastic resin layers is 0.030 or more, more preferably 0.090 or more. If the difference in the in-plane average refractive index is less than 0.03, the reflectance of the reflection band B becomes less than 30%, and the heat shielding property may be insufficient. As a method for achieving this, a method is given in which two types of thermoplastic resin layers are alternately laminated, and the main component of at least one thermoplastic resin is a crystalline resin, and the main component of the other thermoplastic resin layer is amorphous. In this case, it is possible to easily provide a refractive index difference between two types of layers in the stretching and heat treatment steps in the production of the laminated film. Here, the main component refers to a component contained in 60% by mass or more and 100% by mass or less when the entire layer is 100% by mass, and can be interpreted in the same manner below. In addition, adjustment of the number of different thermoplastic resin layers regularly laminated is also effective, and lamination of 401 layers or more is effective for forming the reflection band B.

[0053] To obtain a laminated film having a band in which the reflectance of light incident on the protective layer at an incident angle of 0° is 70% or more continuously over 100 nm or more, it is effective to increase the number of layers after employing a method for obtaining a laminated film having reflection band B. More specifically, it is effective to regularly stack 601 or more layers of different thermoplastic resins.

[0054] Here, the reflective film having the reflection band A and / or the reflection band B, which is used in the base layer of the laminated film of the present invention, will be described in detail by taking an embodiment in which two thermoplastic resin layers are alternately laminated as an example. However, the reflective film is not limited to this.

[0055] The reflective film has a structure in which a layer (layer A) mainly made of a first thermoplastic resin and a layer (layer B) mainly made of a second thermoplastic resin are alternately laminated, and it is preferable that the first thermoplastic resin is a crystalline polyester resin and the second thermoplastic resin is an amorphous polyester resin containing a structure derived from terephthalic acid or naphthalenedicarboxylic acid. In addition, it is preferable that the "amorphous polyester resin containing a structure derived from terephthalic acid or naphthalenedicarboxylic acid" is a polyester resin in which 60 mol % or more and 100 mol % or less of the dicarboxylic acid components constituting the polyester resin are terephthalic acid and / or naphthalenedicarboxylic acid.

[0056] The polyester resin, which is the main component of each layer of the reflective film, may contain a structural unit derived from the following dicarboxylic acid component or diol component. For example, aromatic dicarboxylic acids include terephthalic acid, isophthalic acid, phthalic acid, 1,4-naphthalenedicarboxylic acid, 1,5-naphthalenedicarboxylic acid, 2,6-naphthalenedicarboxylic acid, 4,4'-diphenyldicarboxylic acid, 4,4'-diphenyletherdicarboxylic acid, and 4,4'-diphenylsulfonedicarboxylic acid. Aliphatic dicarboxylic acids include adipic acid, suberic acid, sebacic acid, dimer acid, dodecanedioic acid, cyclohexanedicarboxylic acid, and ester derivatives thereof. These acid components may be used alone or in combination of two or more.

[0057] Examples of the diol component include ethylene glycol, paraxylene glycol, 1,2-propanediol, 1,3-propanediol, neopentyl glycol, 1,3-butanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,2-cyclohexanedimethanol, 1,3-cyclohexanedimethanol, 1,4-cyclohexanedimethanol, diethylene glycol, triethylene glycol, polyalkylene glycol, 2,2-bis(4-hydroxyethoxyphenyl)propane, isosorbate, spiroglycol, bisphenoxyethanolfluorene (BPEF), etc. These diol components may be used alone or in combination of two or more.

[0058] The reflective film can be manufactured by laminating the resins, for example, by the following method. First, two types of thermoplastic resins (or thermoplastic resin compositions) are prepared in the form of pellets or the like. The pellets are dried in hot air or under vacuum as necessary, and then fed to separate extruders. The thermoplastic resin is heated and melted in the extruder at a temperature equal to or higher than its melting point, and the resin is extruded by making the extrusion amount uniform using a gear pump or the like, and then foreign matter and denatured resin are removed through a filter or the like. Next, the two types of thermoplastic resins are fed through separate flow paths into a multi-layer lamination device and laminated alternately.

[0059] As the multi-layer lamination device, a multi-manifold die, a feed block, a static mixer, etc. can be used, but it is particularly preferable to use a feed block having 51 or more, preferably 401 or more, and more preferably 601 or more fine slits. When such a feed block is used, the device does not become extremely large, so there is little foreign matter due to thermal deterioration, and even if the number of layers is extremely large, high-precision lamination is possible. In addition, the lamination accuracy in the width direction is also significantly improved compared to the conventional technology. In addition, with such a device, the thickness of each layer can be adjusted by the shape (length, width) of the slit, and the number of layers can be adjusted by the number of slits, so it is easy to achieve any layer thickness or number of layers. Note that, although the number of layers can be easily increased by increasing the number of slits, the upper limit of the number of slits is preferably 2001 from the viewpoint of avoiding the device becoming large.

[0060] Next, the laminated molten resin is formed into a sheet using a die, and is extruded onto a cooling body such as a casting drum and cooled to solidify, to obtain a cast film. In this case, it is preferable to use a wire-shaped, tape-shaped, needle-shaped, or knife-shaped electrode to bring the molten resin sheet into close contact with a cooling body such as a casting drum by electrostatic force to rapidly solidify it. The temperature and rotation speed of the casting drum are not particularly limited as long as the molten resin can be cooled and solidified, but 20 to 40°C and 1 to 5 m / min are preferable.

[0061] The casting film thus obtained is preferably biaxially stretched. Here, biaxial stretching refers to stretching in the longitudinal direction and the width direction, where the longitudinal direction refers to the running direction of the film and the width direction refers to the direction perpendicular to the longitudinal direction in the film plane. Biaxial stretching may be performed by sequentially stretching in two directions (sequential biaxial stretching) or simultaneously stretching in two directions (simultaneous biaxial stretching). If necessary, re-stretching may be performed in the longitudinal direction and / or the width direction. Sequential biaxial stretching will be described below.

[0062] In the case of sequential biaxial stretching, the stretching speed in the longitudinal direction is preferably 40 to 300% / sec, more preferably 50 to 150% / sec. In general, the stretching in the longitudinal direction is performed by the difference in peripheral speed of the rolls, and the stretching ratio is preferably 1.5 to 5.0 times, more preferably 3.0 to 5.0 times, and even more preferably 3.3 to 5.0 times. The stretching temperature is preferably not lower than the glass transition temperature of the resin having the lower glass transition temperature among the polyester resins of the main components of each layer constituting the casting film to be stretched, and not higher than a temperature 100°C higher than the glass transition temperature of the resin having the lower glass transition temperature, and more preferably not lower than a temperature 3°C higher than the glass transition temperature of the resin having the lower glass transition temperature, and not higher than a temperature 15°C higher than the glass transition temperature of the resin having the lower glass transition temperature. Subsequently, it is preferable to stretch the uniaxially stretched film obtained by the longitudinal stretching in the width direction at a stretching speed of 5 to 40% / sec, more preferably 5 to 30% / sec, and even more preferably 5 to 20% / sec. Generally, the stretching in the width direction is performed using a tenter by conveying the uniaxially stretched film while holding both ends in the width direction with a plurality of clips, and the stretching ratio is preferably 1.5 to 6.5 times, more preferably 3.0 to 5.0 times, and even more preferably 3.4 to 5.0 times. The stretching temperature in the width direction is preferably 7 to 20°C higher than the stretching temperature in the longitudinal direction.

[0063] The sequentially biaxially stretched film is preferably heat-treated in a tenter at a temperature 50°C to 150°C higher than the stretching temperature, and more preferably at a heat treatment temperature of 170°C to 230°C. This allows a film with a desired heat shrinkage ratio to be obtained. In the first half of the heat treatment, additional stretching is performed in the width direction, preferably at a stretching ratio of 1.05 to 1.20 times, and in the second half of the heat treatment, a relaxation treatment is preferably performed in the longitudinal and width directions, preferably at a stretching ratio of 0.90 to 0.99 times (in other words, 1 to 10%) of the film width immediately before relaxation. The multi-layer laminate film thus obtained is then uniformly cooled slowly to room temperature, and the edge portions at both ends in the width direction that were held by the clips of the tenter are cut and wound up. In this way, the above-mentioned reflective film can be obtained.

[0064] The laminated film of the present invention preferably comprises the protective layer on one surface of the base layer, and an adhesive layer on the surface opposite to the protective layer. The adhesive layer here refers to a layer having an adhesive strength of 1 N / cm or more as measured by the 180-degree peel test method described in JISK-6854-2 (1999), and forming the adhesive layer using an adhesive or bonding agent makes it easy to attach the film to a support member. Examples of adhesives and bonding agents include vinyl acetate resins, vinyl chloride-vinyl acetate copolymers, ethylene-vinyl acetate copolymers, polyvinyl alcohol, polyvinyl butyral, polyvinyl acetal, polyvinyl ether, nitrile rubbers, styrene-butadiene rubbers, natural rubbers, chloroprene rubbers, polyamides, epoxy resins, polyurethanes, acrylic resins, cellulose, polyvinyl chloride, polyacrylic esters, polyisobutylene, and other adhesives and bonding agents. Among these, vinyl acetate resins, epoxy resins, and acrylic resins are preferred, as are polyvinyl butyral.

[0065] These pressure sensitive adhesives and adhesives may contain adhesion regulators, plasticizers, heat stabilizers, antioxidants, UV absorbers, antistatic agents, lubricants, colorants, crosslinking agents, etc. The adhesives may be in the form of liquid, gel, block, powder, film, etc. before processing. Methods for solidifying the adhesive layer include solvent evaporation, moisture curing, heat curing, mixing of a curing agent, anaerobic curing, UV curing, thermal melting and cooling, pressure sensitive, etc.

[0066] The laminated film of the present invention preferably has a crack initiation load of 1.0 GPa or more in a scratch test of the outermost layer of the adhesive layer. The harder the adhesive layer is, the less likely the laminated film as a whole will be dented when pressed against it with a pointed member such as a key having a relatively large diameter of 100 μm to 1 mm without being affected by the adhesive layer, and the pressure applied to the protective layer is dispersed, making it less likely to be scratched when scraped.

[0067] Methods for increasing the crack initiation load to 1.0 GPa or more in a scratch test of the outermost layer of the adhesive layer include, for example, chemically increasing the degree of crosslinking of the above-mentioned polymer forming the adhesive layer, or increasing the molecular weight to enhance the entanglement effect of the molecular chains.

[0068] The laminated film of the present invention preferably has an adhesive layer thickness of 5 μm or more and 25 μm or less. The thicker the adhesive layer, the more likely it is to be dented when pressed against the above-mentioned pointed member, etc., and the pressure applied to the protective layer increases, making it more likely to be scratched. Therefore, by making the adhesive layer thinner, 5 μm or more and 25 μm or less, the adhesive layer is prevented from being dented and the occurrence of scratches is suppressed. From the above-mentioned viewpoint, the adhesive layer is preferably thinner, 5 μm or more and 15 μm or less. On the other hand, by making the adhesive layer thicker than 5 μm, peeling from the edge when the laminated film is attached to the support can be reduced. As described above, the microscratch test method in accordance with JIS R-3255: 1997 is preferable for measuring the hardness of the protective layer alone, but the hardness of the entire laminated film including the adhesive layer is preferably measured by the pencil method described in JIS K 5600-5-4 (1999).

[0069] The structure of the present invention will be described below. The structure of the present invention comprises the laminate film of the present invention on at least one side of a support mainly composed of glass or resin. The laminate film of the present invention can be attached to the support by lamination molding, injection molding, autoclave type, vacuum bag type, etc., and is bonded by heating, pressurizing, and solidifying the above-mentioned adhesive layer and pressing it to the support.

[0070] In addition, the area of ​​the laminated film to be attached to the support is not particularly specified, but when it is attached to a part of the support, the refractive index of the laminated film of the present invention and the surface are different, and the boundary is visible, so it is preferable to attach it to the entire support. In particular, it is preferable to attach it to the entire windshield, which is mainly composed of glass. As the main component of the resin support, for example, polyethylene terephthalate, polycarbonate, acrylic, polyvinyl chloride, polyethylene, polypropylene, cycloolefin, polymethylpentene and its copolymer, acrylonitrile-butadiene-styrene copolymer, etc. are preferable.

[0071] Next, the head-up display of the present invention will be described. The head-up display of the present invention comprises an image projector that projects an image, and the structure of the present invention (in other words, a structure comprising a support mainly made of glass or resin and at least one surface of the support having the laminate film of the present invention).

[0072] In the light beams constituting the image from the image projector, it is preferable that the intensity of the P-wave component is 51% or more of the intensity of all light components with respect to the incident surface when the multilayer laminated film is used as the reflection surface. Here, P-waves refer to electromagnetic waves whose electric field components are parallel to the incident surface (linearly polarized light oscillating parallel to the incident surface), and S-waves refer to electromagnetic waves whose electric field components are perpendicular to the incident surface (linearly polarized light oscillating perpendicular to the incident surface). It is preferable that the light beams constituting the image projected from the image projector contain a large amount of P-wave components in order to suppress overlapping images, which are generated when the light is reflected from the front and back surfaces of the projection section (information display section) of the windshield of the transportation equipment and the path of the light beam is shifted, causing the displayed image to appear multiplexed.

[0073] When S waves are included in the light rays that compose the image projected from the image projector, they are reflected on the front and back of the material that composes the information display unit, causing multiple images to be seen. However, when P waves are incident at an angle of incidence close to Brewster's angle, there is almost no reflection on the front and back of the information display unit. In addition, by including a large amount of P waves in the light rays that compose the image projected from the image projector, it is possible to suppress the decrease in brightness of the displayed image even when wearing polarized sunglasses. Polarized sunglasses are designed to block the S wave component in order to suppress the glare from the ground and the windshield, which are dominated by S wave components when the ground surface or water surface is used as a reflective surface, and to ensure a clear field of vision. Therefore, by including a large amount of P waves, which have a polarization direction that differs by 90 degrees, in the light rays that compose the image projected from the image projector, it is possible to maintain the brightness of the displayed image even when wearing polarized sunglasses. From these viewpoints, the higher the ratio of P wave components in the light beam projected from the image projector, the better, more preferably 90% or more, and even more preferably 99% or more. For the reasons mentioned above, there is no particular upper limit to the ratio of P wave components in the light emitted from the projection light source, and it can be substantially 100%.

[0074] The transportation equipment of the present invention will be described below. The transportation equipment of the present invention includes the head-up display of the present invention. The head-up display of the present invention is mounted on transportation equipment, buildings, electronic signboards, etc. for use. The transportation equipment is a means of transportation driven by a passenger, such as an airplane, a ship, an automobile, or a train, and the head-up display of the present invention is incorporated in the windshield of the transportation equipment, for example, the windshield of an automobile, and is used by projecting information required by the passenger on the information display unit. In this case, the positional relationship between the projection light source and the windshield is adjusted so that the image projected from the projection light source is reflected by the information display unit and reaches the field of view of the passenger. The projection incidence angle is preferably in the range of 40 to 75° from the viewpoint of reducing the size of the head-up display and improving visibility, and more preferably 50 to 70°.

[0075] The method for producing the laminated film of the present invention will be described in more detail below with reference to examples. However, the laminated film of the present invention is not limited to the film obtained by the following production method.

[0076] A coating composition containing a desired solvent, binder component, photopolymerization initiator, inorganic particles, other additives, etc. is applied to a reflective film (for example, one produced by the method described above can be suitably used) that will be the base layer. Examples of coating methods include a microgravure method and a die coating method, and it is preferable to apply the coating uniformly in the width direction of the reflective film. It is also preferable to apply the coating uniformly in the width direction with a coating wire bar, and the desired thickness can be achieved depending on the product number and the solid concentration of the coating.

[0077] It is preferable to subsequently volatilize the solvent from the applied coating material in a drying process. Drying methods include heat transfer drying (contact with a hot object), convection heat transfer (hot air), radiation heat transfer (infrared rays), and others (microwaves, induction heating). The drying temperature is preferably within the range of room temperature to 200°C, more preferably 60°C to 200°C, and even more preferably 80°C to 150°C.

[0078] It is preferable to subsequently cure the protective layer. As a curing method, it is preferable to irradiate active energy rays, and as the active energy rays, ultraviolet rays (UV) or electron beams are preferable, and ultraviolet rays are more preferable. The light source of the active energy rays irradiated to thicken the coating film is not particularly limited, but for example, in the case of ultraviolet rays, UV-LED lamps, high pressure mercury lamps, ultra-high pressure mercury lamps, low pressure mercury lamps, metal halide lamps, carbon arc lamps, xenon lamps, etc. may be used as light sources, and two or more of these may be used.

[0079] In addition, a method for transferring a protective layer is also preferred as a method for producing a laminated film. This is a method in which a protective layer sheet including a protective layer and a substrate adhesion layer is pressed against a film to be a substrate layer, and heated while being pressed, thereby transferring the protective layer to the substrate layer. Examples of the substrate adhesion layer include a thermosetting adhesive layer and a heat-sensitive adhesive layer, and the like. From the viewpoint of the processability of the protective layer sheet and the adhesion between the substrate adhesion layer and the substrate layer, a heat-sensitive adhesive layer is preferred.

[0080] When the substrate adhesion layer is a curing adhesive layer, the adhesive layer preferably contains a thermosetting adhesive. The thermosetting adhesive preferably contains a composition that has a property of crosslinking by chemical reaction caused by heat, and examples thereof include a two-component curing urethane adhesive, a polyester urethane adhesive, a polyether urethane adhesive, an acrylic adhesive, a polyester adhesive, a polyamide adhesive, a polyvinyl acetate adhesive, an epoxy adhesive, and a rubber adhesive. The urethane resin constituting the two-component curing urethane adhesive is a polyurethane that uses polyol (polyhydric alcohol) as a main component and isocyanate as a crosslinking agent and curing agent.

[0081] When the substrate adhesive layer is a heat-sensitive adhesive layer, the adhesive layer preferably contains a thermoplastic resin. Examples of the thermoplastic resin include acrylic resin, urethane resin, vinyl chloride resin, vinyl acetate resin, vinyl chloride-vinyl acetate copolymer, styrene-acrylic copolymer, polyester resin, amide resin, cyanoacrylate resin, and epoxy resin, and these can be used alone or in combination. Among these, it is preferable to use an acrylic resin in order to improve the processability when forming a member using the transfer sheet and the adhesion between the transfer layer of the transfer sheet and the substrate.

[0082] As transfer conditions, the pressure is preferably 1.0 GPa or more, and the heating temperature is preferably 100° C. or more, and more preferably 100° C. to 170° C. in consideration of the heat resistance of the base film and the difficulty of processing due to shrinkage. EXAMPLES

[0083] The laminated film of the present invention will be described below using examples, but the laminated film of the present invention is not limited to the following embodiments.

[0084] [Methods for measuring physical properties and evaluating effects] The methods for evaluating the physical properties and the effects are as follows.

[0085] (1) Reflection band and average reflectance of laminated film at an incident angle of 60° (identification of reflection band A) A variable angle reflection unit and a Glan-Taylor polarizer were attached to a Hitachi spectrophotometer (U-4100 Spectrophotometer), and the protective layer side of the laminated film was used as the incident surface, and the reflectance of P waves in the wavelength range of 400 to 2000 nm at an incident angle of θ = 60 ° was measured in 1 nm increments. If the obtained reflection spectrum has a reflection band that is 10% or more continuously over 100 nm or more, the reflection band A is defined as the range between the minimum and maximum wavelengths of the reflection band, and the average reflectance between those wavelengths was calculated. In addition, the average reflectance of the reflection spectrum obtained from 400 to 700 nm was calculated. The measurement conditions were slit: 2 nm (visible) / automatic control (infrared), gain: 2, and scanning speed: 600 nm / min.

[0086] (2) Reflection band and average reflectance of laminated film at an incident angle of 0° (identification of reflection band B) A 60 mmφ integrating sphere was attached to a Hitachi spectrophotometer (U-4100 Spectrophotometer), and the protective layer side of the laminated film was set as the incident surface. The reflectance of a wavelength of 800 to 2000 nm was measured in 1 nm increments when a standard white plate made of aluminum oxide (accessory of U-4100) was set as 100%, to obtain a reflection spectrum. If the obtained reflection spectrum has a reflection band that is 30% or more continuously over 100 nm or more, the range between the minimum and maximum wavelengths of the reflection band was set as reflection band B, and the average reflectance between those wavelengths was obtained. The measurement conditions were slit: 2 nm (visible) / automatic control (infrared), gain: 2, and scanning speed: 600 nm / min.

[0087] (3) Inorganic particle occupancy rate on the outermost surface The measurements were carried out according to the following procedures (A) to (E). (A) The outermost surface of the protective layer of the laminated film was observed at 50,000 times magnification using a scanning electron microscope (JEOL field emission scanning electron microscope (FE-SEM) JSM-6700F), and an image with a field of view of 1900 nm × 2500 nm was obtained. (B) The obtained images were imported into the image analysis software “Image-Pro” 10 (Media Cybernetics), converted to 8-bit grayscale, and subjected to 7 × 7 low-pass image processing. (C) A histogram of the brightness of the processed image was taken, and the observed image was binarized, with areas below the mode brightness designated as black (0% brightness) and areas above the mode brightness designated as white (100% brightness). (D) Using the same image analysis software, count the number of white areas and calculate the area Sw,nw of each white area. 2 The particle occupancy area Sw,total, which is the sum of the white regions as follows, was calculated. (E) The obtained particle occupancy area Sw,total and the image field of view area Sfov (= 1900 × 2500 nm 2 ) and calculated the particle occupancy rate V as shown in Equation 1. Equation 1: V=Sw,total×100 / Sfov.

[0088] (4) Average particle size Using an ion milling device IM4000 (Hitachi High-Technologies Corporation), the film was cut perpendicular to the film surface and parallel to one of the arbitrary directions of the film without crushing it in the thickness direction to prepare measurement samples. Next, the cut surface of each measurement sample was observed using a scanning electron microscope (JEOL Field Emission Scanning Electron Microscope (FE-SEM) JSM-6700F), and SEM images of the protective layer were obtained at a magnification of 10,000 times. The obtained cross-sectional SEM images were imported into the image processing software "Image-Pro" 10 (Media Cybernetics), and the diameters of inorganic particles in the measurement field of view were calculated when converted into perfect circles according to their areas, a histogram of diameters was created, and the most frequent particle size was taken as the average particle size of the inorganic particles.

[0089] (5) Arithmetic mean roughness of protective layer The measurements were carried out according to the following procedures (A) to (C). (A) For a 6 cm x 6 cm laminated film, a scanning white light interference microscope (equipment: Hitachi High-Tech Science Corporation "VertScan" (registered trademark) VS1540) was used to measure the protective layer surface of the laminated film using a 50x objective lens, the measurement mode was set to WAVE mode, the measurement area was 113 μm x 113 μm, and the measurement Y axis was set to any one direction of the sample film, and 90 visual fields were measured. The sample film to be measured was sandwiched between two metal frames containing rubber packing, so that the film in the frame was taut (slack and curl of the sample was removed) and the measurement was performed. (B) The obtained microscopic images were subjected to image processing using the surface analysis software VS-Viewer Version 10.0.3.0 built into the microscope under the following image processing conditions. (Image processing conditions) Interpolation process: Full interpolation Filtering: Median (3x3 pixels) Surface correction: 4th order (C) For each measurement image that was processed under the above image processing conditions, select "Height Parameters" along with the following analysis conditions in the ISO parameter analysis in the surface analysis software, and output the obtained numerical values ​​in the parameter sheet column to obtain the arithmetic mean height Sa, which was used as the arithmetic mean roughness of the protective layer of each laminated film. The arithmetic mean roughness was calculated for 80 visual fields, excluding the top and bottom five visual fields from each visual field, and the obtained average value was used.

[0090] (6) Pressure at which cracks occur in protective layers and adhesive layers The micro-scratch test was performed according to JIS R-3255: 1997. Specifically, a 4 cm x 4 cm square laminated film was prepared and placed on the measurement stage of a scratch tester (CSR5000 manufactured by Rhesca) with the protective layer or adhesive layer facing the stylus, and a surface scratch test was performed under the following conditions. Stylus: Diamond stylus (stylus diameter 15 μm) Scratch speed: 10μm / sec Excitation amplitude: 50μm Excitation frequency: 45Hz Touch detection level: 3.0mN Load condition: monotonic increase (+1,33mN / sec) Initial load: 0mN Maximum load: 100mN Measurement time: 600 seconds Measurement environment: 25℃, relative humidity 65%.

[0091] The load at which the vertical sensor acceleration value (unitless) exceeded 200 for the first time during the time-dependent change from the start of measurement was defined as the fracture initiation load. If the acceleration did not exceed 200 during the second measurement, the crack initiation pressure was set to 800 mN. The crack initiation pressure was calculated from the obtained load and the diameter of the stylus using Equation 2. Equation 2: Crack initiation pressure (GPa) = Crack initiation load (mN) ÷ (15 ÷ 2) 2 ÷π × 1000.

[0092] (7) Thermal shrinkage rate when heat treated at 150°C for 30 minutes The laminated film was cut into 150 mm x 10 mm pieces at an arbitrary position and direction (sample position 1). Next, the film was cut into 150 mm x 10 mm pieces so that the long-length direction was at a position (sample position 2) where the angle between sample position 1 and the long-length direction was 10° counterclockwise. Similarly, the film was cut into 150 mm x 10 mm pieces so that the long-length direction was at a position (sample position 3) where the angle between sample position 2 and the long-length direction was 10° counterclockwise. The same operation was repeated eight more times to obtain sample pieces at sample positions 1 to 10. These sample pieces were left in an atmosphere of 23°C and 60% relative humidity for 30 minutes, and two marks were made on the sample pieces at an interval of about 100 mm in the long-length direction under that atmosphere. The distance between the two marks was measured using a Nikon universal projector (Model V-16A), and the value was designated as A. Next, each sample piece was left in a tension-free state in an atmosphere at 150°C for 30 minutes, then cooled and conditioned in an atmosphere at 23°C and relative humidity of 60% for 1 hour, after which the distance between the two marks made earlier was measured and designated as B. Using A and B of each obtained sample, the thermal shrinkage rate was calculated from the following formula 3. Among the thermal shrinkage rates at sample positions 1 to 10, the maximum value was adopted as the thermal shrinkage rate when the laminated film was heat-treated at 150°C for 30 minutes. Equation 3: Heat shrinkage rate(%)=100×(AB) / A.

[0093] (8) Adhesive layer thickness (4) Using the same method as for measuring the average particle size, the cut surface of each laminate film was observed, and SEM images of the adhesive layer were obtained at a magnification of 1,000 times. The obtained cross-sectional SEM images were imported into the image processing software "Image-Pro" 10 (Media Cybernetics), and the thickness of the adhesive layer was measured using the length measurement function of the image processing software.

[0094] (9) Abrasion resistance test A 10cm square glass laminate sample was obtained by manually attaching the laminate film with Tomoegawa Paper's high hardness adhesive TA-Z74 (adhesive A) or the same company's optical adhesive TD-06A (adhesive B) using a roller at room temperature. Next, a test cloth was pressed against the protective layer side of the glass laminate sample and rubbed under the following rubbing conditions, and the occurrence of scratches was observed after a specified number of back and forth strokes to determine the number of times that at least one scratch occurred. The minimum pass mark is no scratches after 1000 strokes, and the more tests that occur before scratches occur, the better the abrasion resistance. <Rubbing conditions> Test cloth: TRIBOTOUCH TT-STex (wool) Travel amount: 20mm Traveling speed: 50mm / sec Pressing area: 6.5mm x 6.5mm Stress: 74kPa Observe for scratch occurrence: every 100 strokes up to 1000 strokes, every 1000 strokes from 1000 to 30000 strokes, and every 5000 strokes from 30000 strokes.

[0095] (10) Heat processing test Each laminated film was attached to a glass having a unidirectional curved surface structure of 15cm x 20cm x 1cm and R400 in the same manner as in (9) to prepare a sample, which was then left to stand at 150°C for 2 hours, cooled to room temperature, and the appearance was checked and the number of cracks in the protective layer was counted. The evaluation criteria were as follows: ○:0 bottles △: 1 to 3 ×: 4 or more.

[0096] (11)Pencil hardness The glass laminate sample obtained in the same manner as in (9) was left to stand at 20°C for 12 hours, and then the surface hardness of the laminated film was measured in the same environment according to the scratch hardness (pencil method) described in JIS K 5600-5-4 (1999).

[0097] (12) Internal haze A sample of the laminated film was placed in a quartz cell for liquid measurement with the protective layer facing the light source, filled with liquid paraffin, and measured (JIS K 7136:2000) using a haze meter (HGM-2DP) manufactured by Suga Test Instruments Co., Ltd. The measurement was repeated 10 times at randomly changed measurement positions, and the average value was taken as the internal haze value.

[0098] (13) Head-up display (HUD) A HUD system was fabricated that was equipped with a glass laminate sample obtained in the same manner as in (9) and a projection light source that generates and radiates P waves. The information display performance was evaluated visually when an image was projected at an incident angle of 60°. The evaluation criteria are as follows: .circle.: The image projected onto the projection image display member was very clearly visible. A: The image projected onto the projection image display member was clearly visible. Δ: The image projected onto the projection image display member was poor in clarity, but was slightly visible. ×: The image projected onto the projection image display member had poor clarity and was not visible.

[0099] (14) Visibility of the outside view A glass laminate sample was prepared in the same manner as in (9), and tilted at an angle of 60° from the vertical direction. The visibility of the outside scenery was evaluated visually through the glass laminate sample. The evaluation criteria are as follows: ◎: The outside view can be seen clearly. ○: The clarity is poor, but the outside scenery can be seen without any problems. △: The outside scenery can be seen to some extent. ×: The outside view cannot be seen.

[0100] [Resins used to obtain multi-layer laminated film] To obtain the laminated films of each Example and Comparative Example, the resins shown in Table 1 and the hard coat coating materials shown in Table 2 were used. "mol %" is the ratio of the dicarboxylic acid unit and the diol unit, respectively, with the total amount taken as 100 mol %.

[0101] [Table 1]

[0102] [Table 2]

[0103] [Reflection film A] First, a reflective film was obtained by the following procedure. Polyethylene terephthalate (resin 1) was used as thermoplastic resin A. A copolymer of polyethylene terephthalate (polyethylene terephthalate copolymerized with 80 mol% of terephthalic acid component relative to the total acid component and 20 mol% of 2,6-naphthalenedicarboxylic acid component relative to the total acid component) (resin 2) was used as thermoplastic resin B. The prepared thermoplastic resin A and thermoplastic resin B were respectively fed into two single-screw extruders and melted at a temperature of 280°C. Next, the thermoplastic resin A and thermoplastic resin B were passed through five FSS-type leaf disk filters, respectively, and then, while being metered by a gear pump, were joined in a lamination device with 801 slits so that the mass ratio (A / B) of thermoplastic resin A to thermoplastic resin B was 1, to obtain a molten resin laminate in which 801 layers were alternately laminated in the thickness direction so that thermoplastic resin A was located in the outermost layer on both sides. Thereafter, the molten resin laminate was discharged from a die, cooled and solidified on a casting drum at a temperature of 25°C to obtain a cast film. The obtained cast film was heated with a group of rolls set at a temperature of 60 ° C, and then stretched 3.3 times in the longitudinal direction of the film with rolls set at a temperature of 87 ° C at a stretching speed of 50% / sec, and then cooled once. The uniaxially stretched film thus obtained was introduced into a tenter, preheated with hot air at 90 ° C, and then stretched 3.4 times in the film width direction at a stretching speed of 5% / sec at 95 ° C. The stretched film was heat-treated with hot air at 210 ° C in the tenter as it was, and then subjected to a 3% relaxation treatment (Rx) in the width direction under the same temperature conditions, and then cooled to room temperature. In this way, a reflective film A with a thickness of 80 μm was obtained. The evaluation results are shown in Table 3.

[0104] [Reflection film B~G] It was produced in the same manner as Reflective Film A, except that the number of layers, the resin of each layer, and the film-forming conditions were as shown in Table 3. The evaluation results are shown in Table 3. The thickness of the film was adjusted by the take-up speed of the cast drum, and the number of layers was adjusted by the number of slits in the lamination device. Reflective Film E was produced by supplying the same type of resin to each extruder.

[0105] [Table 3]

[0106] Example 1 A protective layer was laminated on the obtained reflective film A by the following procedure. A hard coat paint was obtained by mixing 67 mass% of Momentive Material Performance Hard Coat UVHC7400 (HC-A) and 33 mass% of Nippon Shokubai Nanoparticles (20 nm silica particles) IX-3-TR-M-02-J. This hard coat paint was applied to the reflective film using RD Specialties Stainless Steel Coating Wire Bar #12 and left to stand in a high temperature tank at 100°C to volatilize the solvent. Next, the film was exposed to a UV irradiation device (Eye Graphics ECS-401GX) with an accumulated light dose of 770 mj / cm. 2 The film was irradiated with UV light so that the hard coat layer was cured to a total thickness of 10 μm. The hard coat layer was then cured in the same manner using the company's hard coat paint UVHC7300 (HC-C) with wire bar #2, and a 2 μm-thick top coat layer was laminated to obtain a laminated film having a protective layer consisting of two hard coat layers. The evaluation results are shown in Table 4-1.

[0107] (Examples 2 to 21, Comparative Examples 1 to 4) The type of reflective film, the coating material and layer structure used to form the protective layer were as shown in Tables 4-1 to 4-3, and a laminate film was obtained in the same manner as in Example 1, except that no topcoat layer was formed. The evaluation results are shown in Tables 4-1 to 4-3.

[0108] [Table 4-1]

[0109] [Table 4-2]

[0110] [Table 4-3]

[0111] In the abrasion resistance test, "100x" means that scratches occurred after 100 cycles. [Industrial Applicability]

[0112] According to the present invention, it is possible to provide a laminate film that reduces appearance defects when attached to the outermost surface of a windshield of a transport device and has abrasion resistance, and a laminate film that has both heat insulation and abrasion resistance. Due to the above properties, the laminate film of the present invention can be suitably used for head-up displays and the like.

Claims

1. A laminated film comprising a protective layer on at least one surface of a base layer, and at least one reflection band (reflection band A) in which the reflectance of P waves incident on the protective layer under conditions of a wavelength of 400 to 2000 nm and an incident angle of 60° is 10% or more continuously over 100 nm or more, the concentration of inorganic particles in the protective layer is 10% by mass or more and 60% by mass or less, and the inorganic particle occupancy rate of the outermost surface of the protective layer is 0.1% by mass or more and 60% by mass or less.

2. The laminated film according to claim 1 , wherein the inorganic particles have an average particle size of 5 nm or more and 60 nm or less.

3. The laminate film according to claim 1 or 2, wherein the protective layer has an arithmetic mean roughness of 0.10 nm or more and 0.90 nm or less.

4. 3. The laminated film according to claim 1, wherein the protective layer has a crack initiation pressure of 100 GPa or more and 600 GPa or less, as determined by a microscratch test method in accordance with JIS R-3255:1997.

5. 3. The laminated film according to claim 1, which has a heat shrinkage rate of 1.0% or more and 3.0% or less when heat-treated at 150° C. for 30 minutes.

6. 3. The laminated film according to claim 1, wherein the average reflectance of P waves having a wavelength of 400 to 700 nm incident on the protective layer at an incident angle of 60° is 10% or more.

7. 3. The laminate film according to claim 1, having at least one reflection band (reflection band B) in which the reflectance of light incident on the protective layer under conditions of a wavelength of 800 to 2000 nm and an incident angle of 0° is 30% or more continuously over a range of 100 nm or more.

8. The laminated film according to claim 1 or 2, further comprising the protective layer on one surface of the base layer, and an adhesive layer on the surface opposite to the protective layer.

9. The laminated film according to claim 8 , wherein the adhesive layer has an outermost layer crack initiation load of 1.0 GPa or more in a scratch test.

10. The laminated film according to claim 8 , wherein the adhesive layer has a thickness of 5 μm or more and 25 μm or less.

11. A structure comprising the laminate film according to claim 8 on at least one surface of a support mainly composed of glass or resin.

12. A head-up display system comprising: an image projector for projecting an image; and the arrangement according to claim 11.

13. 13. The head-up display system according to claim 12, wherein in the light beam projected from the image projector, the intensity of the P-wave component is 51% or more of the intensity of all light beam components.

14. A transport device comprising the arrangement of claim 11.

Citation Information

Patent Citations

  • Head-up display with polarized light source and wide-angle p-polarized reflective polarizer

    JP2006512622A

  • Hard coat film

    JP2009042647A

  • Laminate film and foldable device

    JP2022081716A